Distinct Facets of Impulsivity Exhibit Differential Associations with Substance Use Disorder Treatment Processes: A Cross-Sectional and Prospective Investigation Among Military Veterans - Heinz, Adrienne J. (J Subst Abuse Treat, 2015)
Impulsivity, a multi-faceted construct characterized by rash, unplanned actions and a disregard for long-term consequences, is associated with poor substance use disorder (SUD) treatment outcomes. Little is known though about the influence of impulsivity on treatment process variables critical for initiating and maintaining behavioral change. This knowledge gap is important as different aspects of impulsivity may be susceptible to diverse cognitive, behavioral and pharmacological influences. The present study examined two distinct facets of impulsivity (lack of planning and immoderation - a proxy of urgency) as predictors of processes that impact SUD treatment success (active coping, avoidant coping, self-efficacy, and interpersonal problems). Participants were 200 Veterans who completed impulsivity and treatment process assessments upon entering a SUD treatment program and treatment process assessments at treatment discharge. Results from multivariate models revealed that lack of planning was associated with lower active coping and higher avoidant coping and interpersonal problems at intake, though not with lower self-efficacy to abstain from substances. Immoderation was associated with higher avoidant coping and lower self-efficacy to abstain from substances at intake, but not with lower active coping or higher interpersonal problems. Higher immoderation, but not lack of planning, predicted lower self-efficacy to abstain from substances at treatment discharge. These findings suggest that different facets of impulsivity confer risk for different SUD treatment process indicators and that clinicians should consider the behavioral expression of patients’ impulse control problems in treatment planning and delivery.